Anti–B-cell maturation antigen bite molecule AMG 420 induces responses in multiple myeloma - Topp, Max S.; Duell, Johannes; Zugmaier, Gerhard; Attal, Michel; Moreau, Philippe; Langer, Christian; Kroenke, Jan; Facon, Thierry; Salnikov, Alexey V.; Lesley, Robin; Beutner, Karl; Kalabus, James; et al. (Journal of Clinical Oncology, 2020)
PURPOSE The anti–B-cell maturation antigen BiTE molecule AMG 420 was assessed in patients with relapsed/ refractory multiple myeloma. PATIENTS AND METHODS In this first-in-human study, up to 10 cycles of AMG 420 were given (4-week infusions/ 6-week cycles). Patients had progression after 2 lines of prior therapy and no extramedullary disease. Minimal residual disease (MRD) response was defined as, 1 tumor cell/104 bone marrow cells by flow cytometry. RESULTS Forty-two patients received AMG 420 at 0.2-800 mg/d. Median age was 65 years, and median disease duration was 5.2 years. Median exposure was 1 cycle (range, 1-10 cycles) and 7 cycles (range, 1-10 cycles) for responders. Patients discontinued for disease progression (n = 25), adverse events (AEs; n = 7), death (n = 4), completion of 10 cycles (n = 3), and consent withdrawal (n = 1). Two patients remain on treatment. There were 2 nontreatment-related deaths from AEs, influenza/aspergillosis and adenovirus-related hepatitis. Serious AEs (n = 20; 48%) included infections (n = 14) and polyneuropathy (n = 2); treatment-related serious AEs included 2 grade 3 polyneuropathies and 1 grade 3 edema. There were no grade 3 CNS toxicities or anti-AMG 420 antibodies. In this study, 800 mg/d was considered to not be tolerable because of 1 instance each of grade 3 cytokine release syndrome and grade 3 polyneuropathy, both of which resolved. The overall response rate was 31% (n = 13 of 42). At the maximum tolerated dose (MTD) of 400 mg/d, the response rate was 70% (n = 7 of 10). Of these, five patients experienced MRD-negative complete responses, and 1 had a partial response, and 1 had a very good partial response; all 7 patients responded during the first cycle, and some responses lasted . 1 year. CONCLUSION In this study of AMG 420 in patients with relapsed/refractory multiple myeloma, the response rate was 70%, including 50% MRD-negative complete responses, at 400 mg/d, the MTD for this study.
CRIS-Team Scopus Importer:2023-03-23